Effects of Hyperoxia on the Refraction in Murine Neonatal and Adult Models - Mori, Kiwako (Int J Mol Sci, 2019)
Whether hyperoxia affects the refraction in neonatal and adult mice is unknown. The mice exposed to 85% oxygen at postnatal 8 days (P8d) for 3 days and the mice exposed to normal air were assigned to the neonatal hyperoxia and normoxia groups, respectively. The refraction, the corneal curvature radius (CR) and the axial length (AL) were measured at P30d and P47d. Postnatal 6 weeks (P6w) adult mice were divided into the adult hyperoxia and normoxia groups. These parameters were measured before oxygen exposure, after 1 and 6 weeks, and every 7 weeks. The lens elasticity was measured at P7w and P26w by enucleation. The neonatal hyperoxia group showed a significantly larger myopic change than the neonatal normoxia group (P47d −6.56 ± 5.89 D, +4.11 ± 2.02 D, p < 0.001), whereas the changes in AL were not significantly different (P47d, 3.31 ± 0.04 mm, 3.31 ± 0.05 mm, p = 0.852). The adult hyperoxia group also showed a significantly larger myopic change (P12w, −7.20 ± 4.09 D, +7.52 ± 2.54 D, p < 0.001). The AL did not show significant difference (P12w, 3.44 ± 0.03 mm, 3.43 ± 0.01 mm, p = 0.545); however, the CR in the adult hyperoxia group was significantly smaller than the adult normoxia group (P12w, 1.44 ± 0.03 mm, 1.50 ± 0.03 mm, p = 0.003). In conclusion, hyperoxia was demonstrated to induce myopic shift both in neonatal and adult mice, which was attributed to the change in the CR rather than the AL. Elucidation of the mechanisms of hyperoxia and the application of this result to humans should be carried out in future studies.